The Metaphorical Translation's Analysis in Soundtrack Lyrics "The Disney Aladdin 2019 Movie" - Rina Kartika (MEDIOVA: Journal of Islamic Media Studies, 2021)
This study discusses The Metaphorical Translation’s Analysis in Soundtracks Lyrics "The Disney Aladdin 2019 Movie". The purpose of this study is that to discover the types of metaphors and the strategies that are translators used in translating the metaphors. The metaphors found are classified based on Newmark theory, and the strategies used when translating metaphors from source Language to Target languages are classified using Larson theory. The data is collected by finding the metaphorical expressions in the lyrics of the soundtrack the Disney Aladdin 2019 Movie from English to Indonesian. This study uses qualitative descriptive methods. The results show that there are 5 of 6 types of metaphor found and the most used strategy is the metaphor can be kept if the receptor language permits